Identification of neoantigens in oesophageal adenocarcinoma. Issue 3 (19th October 2022) - Nicholas, Ben; Bailey, Alistair; McCann, Katy J.; Wood, Oliver; Walker, Robert C.; Parker, Robert; Ternette, Nicola; Elliott, Tim; Underwood, Tim J.; Johnson, Peter; Skipp, Paul
Abstract: Oesophageal adenocarcinoma (OAC) has a relatively poor long‐term survival and limited treatment options. Promising targets for immunotherapy are short peptide neoantigens containing tumour mutations, presented to cytotoxic T‐cells by human leucocyte antigen (HLA) molecules. Despite an association between putative neoantigen abundance and therapeutic response across cancers, immunogenic neoantigens are challenging to identify. Here we characterized the mutational and immunopeptidomic landscapes of tumours from a cohort of seven patients with OAC. We directly identified one HLA‐I presented neoantigen from one patient, and report functional T‐cell responses from a predicted HLA‐II neoantigen in a second patient. The predicted class II neoantigen contains both HLA I and II binding motifs. Our exploratory observations are consistent with previous neoantigen studies in finding that neoantigens are rarely directly observed, and an identification success rate following prediction in the order of 10%. However, our identified putative neoantigen is capable of eliciting strong T‐cell responses, emphasizing the need for improved strategies for neoantigen identification. Abstract : Oesophageal adenocarcinoma (OAC) has a relatively poor long‐term survival and limited treatment options. Here we characterized the mutational and immunopeptidomic landscapes of tumours from a cohort of seven patients with OAC. We directly identified one HLA‐I presented neoantigen from one patient, and report functional T‐cell responses from a predicted HLA‐II neoantigen in a second patient containing both HLA I and II binding motifs.